PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN NASABAH MEMILIH PEMBIAYAAN KPR DI BANK BTN SYARIAH CABANG MEDAN: Pengaruh Kualitas Produk Terhadap Keputusan Nasabah Memilih Pembiayaan KPR Di Bank BTN Syariah Cabang Medan - Dwi Vanka Br. Sitepu; Raja Sakti Putra Harahap (Program Studi Ekonomi Syariah, 2025)
Sharia financing with a more certain installment amount makes it one of the people's interests to take out a mortgage at Bank BTN Syariah Medan Branch Office. The question in this research is, is the quality of Sharia financing products with more definite installment amounts able to influence customers' decisions when choosing Home Ownership Credit (KPR) at Bank BTN Syariah Medan Branch Office? The method used in this research is quantitative, with a sample of 41 respondents. This research shows that the product quality variable significantly influences the decision to occupy a house at Bank BTN Syariah Medan Branch Office. This is also proven by the Product Quality Variable (X) having a tcount of 4.781 with a significance level of 0.006 and a ttable of 1.682 with df = 41 at the 0.05 level. The significance level is less than 0.05. The coefficient of determination results shows that 63.7% of location variables can influence the decision variable to occupy a house, and other variables outside the research discussion influence the remaining 36.3%.